P162 Microscopic inflammation in limited Ulcerative Colitis at diagnosis: can a single histological feature predict prognosis?. (27th May 2021) - Revés, J; Frias Gomes, C; Ellul, P; Callé, C; Almeida, A; Burisch, J; Buhagiar, T; Attard, A; Lo, B; Ungaro, R; Morão, B; Gouveia, C; et al.
Abstract: Background: Histological assessment is becoming increasingly important in the management of Ulcerative Colitis (UC). The Nancy index (NI), a recently developed and validated score, has been shown to accurately represent histological inflammation and to correlate with prognosis. However, it is a composite score, involving the analysis of more than one histological feature, which may limit its applicability. Our aim was to evaluate if a single component of the NI could individually predict prognosis in limited UC (E1 and E2) patients. Methods: Multi-centre retrospective cohort study of newly diagnosed, treatment-naïve proctitis and left-sided ulcerative colitis patients. Biopsies from inflamed rectal mucosa were reviewed by two pathologists. Histological features from the NI were selected for analysis, including presence of ulcers, acute inflammatory infiltrate (with separate evaluation of neutrophils in lamina propria and epithelium) and chronic inflammatory infiltrate. Mucin depletion and basal plasmacytosis were also evaluated. The primary outcome was a composite outcome intended to evaluate disease-related complications, including proximal disease extension, need for hospitalisation or colectomy. Survival analysis, including univariate and multivariate Cox-regression analysis was performed. Results: A total of 91 patients were included (56.0% males, mean age 44±17 years, median follow-up 44 months [2–328]). Overall, 64.8% of the patients had proctitis (E1) and 35.2% left-sided colitis (E2). The most frequent histological features were the presence of chronic inflammatory infiltrate (93.4%), mucin depletion (81.3%) and basal plasmacytosis (78.0%). During the follow-up, 22.0% presented a disease-related complication. The NI was not able to predict prognosis (HR 3.09, 95% CI 0.71–13.36, p=0.132). In univariate analysis, the presence of neutrophils in the epithelium in more than 50% of the crypts was marginally significant for the primary outcome (HR 2.51, 95% CI 0.99–6.36, p=0.05). In multivariate analysis, after adjusting for gender, age at diagnosis, disease extent (E1 vs E2), Mayo endoscopic score (< 2 vs ≥ 2) and clinical severity at diagnosis (mild vs moderate to severe UC) this single component of the score was associated with the primary outcome (aHR 3.36, 95% IC 1.21–9.31, p=0.02). No other histological feature was able to individually predict prognosis (p>0.05). Conclusion: The presence of neutrophils in the epithelium in more than 50% of the crypts in endoscopically inflamed mucosa at diagnosis was associated with higher disease complications in limited UC patients. The evaluation of a single feature could facilitate the use of histology in the prediction of prognosis in UC. Our results need to be prospectively validated.